Food quality and shelf life - Galanakis, Charis M. (Academic Press, an Imprint of Elsevier, 2019)
"Food Quality and Shelf Life is an integral reference that covers all challenges of shelf life regarding the quality of final food products. It provides practical information on the most trending areas in the field, starting with the various quality changes that occur during shelf life. It deals with water content and stability of food ingredients, emerging cold pasteurization technologies, natural antimicrobials potentially useful for food preservation, improving shelf life with encapsulation of ingredients, survival of probiotics in functional foods during their shelf life, active, intelligent, and modified atmosphere packaging, and fruit and vegetable pre-harvest and postharvest quality assessment with non-destructive techniques. Researchers, professionals, and anyone interested in food preservation and food quality will find this reference useful. Food Quality and Shelf Life is especially helpful to those who are interested in performance evaluation of future packaging for fresh produce in the cold chain and those who aspire to maintain fresh-like properties in minimally processed and tailor-made foods"--